Effects of complexing agents on electrochemical deposition of FeSxOy thin films - Supee, A. (Japan Society of Applied Physics, 2016)
FeSxOy thin films were deposited on indium-tin-oxide (ITO)-coated glass substrates at 15 °C via galvanostatic electrochemical deposition from an aqueous solution containing 100mM Na2S2O3 and 30mM FeSO4. The effects of L(+)-tartaric acid (C4H4O6) and lactic acid [CH3CH(OH)COOH] at different concentrations were investigated. All the deposited films were amorphous. With the complexing agents, the thickness was increased, and the oxygen content was reduced significantly compared with the sample deposited without the complexing agents. In the photoelectrochemical measurement, p-type conductivity was confirmed. The photoresponsivity was not influenced significantly by the complexing agent, suggesting that the oxygen content does not drastically affect the properties of the deposited films probably because the local bonding configuration around Fe atoms in FeSxOy is similar to that in FeS2.